Penggunaan Media Video Dan Teka-Teki Silang Dalam Pembelajaran Tematik Pada Siswa Kelas III SD Negeri 3 Wonoboyo - Yoga Pratama, Dhama (STABN RADEN WIJAYA WONOGIRI JAWA TENGAH, 2023)
Thematic learning is learning based on a theme that is used to associate several subject concepts. Video-based learning media is an effective tool in conveying information and concepts to students using a moving visual format. Crossword puzzle media is a creative and interactive tool that can be used in learning to teach and test students' understanding of various concepts, words, or specific topics. This study aims to provide information on the application of video media and crossword puzzles in thematic learning in grade III students of SD Negeri 3 Wonoboyo.